Convenient one-pot synthesis and biological evaluation of phosphoramidates and phosphonates containing heterocycles. (3rd July 2018) - Nayab Rasool, SK.; Subramanyam, Ch.; Janakiramudu, D. B.; Supraja, P.; Usha, R.; Raju, C. Naga
GRAPHICAL ABSTRACT: ABSTRACT: A series of new phosphoramidates and phosphonates were synthesized in single step by reacting diethyl phosphorochloridate with various bioactive amines. The newly synthesized compounds3a-j were tested for antibacterial activity against Gram-positive and Gram-negative bacteria. All the title compounds exhibited good activity. Amongst all the tested compounds, 3b (diethyl(4-(6-fluorobenzo(d)isoxazol-3-yl)piperidin-1-yl)phosphonate), 3c (diethyl 4, 6-difluorobenzo(d)thiazole-2-ylphosphoramidate) and3d (diethyl 5-nitro-1 H -indazol-1-yl- phosphonate) displayed promising antimicrobial activity against Pseudomonas aeruginosa and Trichoderma viride due to the presence of electron with drawing fluoro and nitro groups respectively.